In Vitro/In Vivo Evaluation of Clomipramine Orodispersible Tablets for the Treatment of Depression and Obsessive-Compulsive Disorder - Shazia Akram Ghumman; Huma Hameed; Sobia Noreen; Sami A. Al-Hussain; Rizwana Kausar; Ali Irfan; Ramla Shabbir; Maria Rana; Amina Amanat; Magdi E. A. Zaki (MDPI AG, 2023)
The first and only antidepressant drug on the market with solid proof of clinically significant serotonin and noradrenaline reuptake inhibition is clomipramine (CLP). However, significant first-pass metabolism reduces its absorption to less than 62%. It is heavily protein-bound and broadly dispersed across the body (9-25 L/kg volume of distribution). The purpose of this research was to formulate CLP orodispersible tablets that immediately enable the drug to enter the bloodstream and bypass systemic portal circulation to improve its bioavailability. A factorial design was employed using varied amounts of Plantago ovata mucilage (POM) as a natural superdisintegrant, as well as croscarmellose sodium and crospovidone as synthetic disintegrants. Their physiochemical compatibility was evaluated by FTIR, DSC/TGA, and PXRD analysis. The blend of all formulations was assessed for pre- and post-compaction parameters. The study found that tablets comprising Plantago ovata mucilage as a superdisintegrant showed a rapid in vitro disintegration time, i.e., around 8.39 s, and had an excellent dissolution profile. The anti-depressant efficacy was evaluated by an open-field test (OFT) and the forced swimming test (FST) was applied to create hopelessness and despair behavior as a model of depression in animals (Albino rats). The in vivo study revealed that the efficiency of the optimized formulation (F9) in the treatment of depression is more than the marketed available clomfranil tablet, and may be linked to its rapid disintegration and bypassing of systemic portal circulation.